Citalopram Protects Against Cold-Restraint Stress-Induced Activation of Brain-Derived Neurotrophic Factor and Expression of Nuclear Factor Kappa-Light-Chain-Enhancer of Activated B Cells in Rats - Garabadu D.; Reddy B.C.M.H.; Krishnamurthy S. (My University, 2025)
The present study evaluates the protective effect of citalopram against cold-restraint stress (CRS) paradigm. Rats were pretreated with citalopram (0.1, 1.0, and 10.0 mg/kg) acutely and repeatedly for 21 days before exposure to the CRS procedure. None of the doses of citalopram attenuated CRS-induced gastric ulcers in the acute study. In contrast, repeated pretreatment of citalopram at a dose level of 0.1 mg/kg attenuated the CRS-induced gastric ulcers. Citalopram (0.1 mg/kg) diminished CRS-induced increase in plasma corticosterone, but not plasma norepinephrine level in the chronic study indicating its effect on hypothalamic-pituitary-adrenal axis function. Repeated citalopram (0.1 mg/kg) pretreatment attenuated CRS-induced changes in serotonin turnover in the hippocampus and amygdala. Moreover, repeated pretreatment with citalopram (0.1 mg/kg) mitigated the CRS-induced increase in the expression of brain-derived neurotrophic factor (BDNF) and nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) in the hippocampus and amygdala. These results suggest that there is a region- and a dose-specific effect of citalopram on CRS-induced BDNF-NFκB activation. Therefore, citalopram showed antistress activity in the CRS model through changes in the stress-responsive pathways such as hypothalamic-pituitary-adrenal-axis and brain serotonergic system apart from decreasing the expression of BDNF and NFκB. © 2014, Springer Science+Business Media New York.